Implementasi Model Pentahelix Dalam Pengembangan UMKM Dimasa Pandemi Covid-19 - Ishak, Parmin; Sholehah, Nur Lazimatul Hilma (Gorontalo Accounting Journal, 2021)
This study aims to determine the extent of the implementation of the pentahelix model in the development of SMEs during the COVID-19 pandemic in Wonosari District.Datawas collected through interviews, documentation and literature study. The results of this study indicate that the development of SMEs in Wonosari District using the pentahelix model has involved five stakeholders, namely the government, academia, community, business and media. Although the five stakeholders have not been optimal in carrying out their respective roles. What is lacking in the pentahelix model is the coordination between stakeholders which is still conditional. This should be a concern for the government as the leading sector to coordinate all stakeholders. As well as the need for monitoring and evaluation from the government in carrying out the program. This paper is expected to contribute to the development of SMEs in the Wonosari sub-district.